The metacognitive student : how to teach academic, social, and emotional intelligence in every content area - Cohen, Richard K.; Opatosky, Deanne Kildare; Savage, James; Stevens, Susan Olsen; Darrah, Edward P. (Solution Tree Press, 2021)
"Stress and anxiety run rampant through modern schools, with both teachers and students dealing with seemingly unmanageable volumes of both daily. A common solution many school districts have tried is to introduce social-emotional learning (SEL) as part of school curricula, which has proven to help with stress and anxiety levels. However, SEL is challenging for teachers to implement effectively, often adding more stress to overwhelmed students and teachers than it takes away. Teachers need a way to practice and teach SEL simultaneously with academic content in order to achieve balance. To address this need, authors Richard K. Cohen, Deanne Kildare Opatosky, James Savage, Susan Olsen Stevens, and Edward P. Darrah developed a simple, flexible strategy teachers and students can utilize as part of any academic content area and any grade level. The Metacognitive Student: How to Teach Academic, Social, and Emotional Intelligence in Every Content Area explains how teachers can learn and use with students a metacognitive approach the authors call structured SELf-questioning. With this strategy, students and teachers learn how to stop and think about their thinking (metacognition) and weave critical-thinking and problem-solving skills into everyday learning to increase self-awareness, self-management, social awareness, and responsible decision making. Through a metacognitive approach utilizing SELf-questioning, stress and anxiety lose their hold on classrooms so that effective education can thrive"--